Contribuição à análise de fadiga de sistemas estruturais incorporando materiais viscoelásticos - Ramos, Ana Paula Rodrigues (2014)
This work is dedicated to computational implementation and numerical study of viscoelastic materials applied as surface viscoelastic treatments by constraining layers in order to increase the fatigue life of engineering structures subjected to stationary and Gaussian random excitations. In the development of theory a three-layer sandwich plate element to be combined with the so-named Frequency-Temperature Superposition Principle is used in order to introduce the frequency- and temperature-dependent behavior of the viscoelastic material. Regarding the fatigue criterion, in the present study it will be adopted the Sines global criterion that enables to perform fatigue analyses of engineering systems subjected to multiaxial and non-proportional loads. The results are obtained in terms of stress responses and frequency response functions computed for the systems with and without viscoelastic damping, and the distributions of the fatigue criterion. The responses of the viscoelastic system are computed by using a condensation strategy adapted to viscoelastically damped structures in which the basis is formed the normal modes of the associated conservative system enriched by static residues due to the external loadings and the viscoelastic damping forces. Finally, the obtained results in terms of the stress responses and the fatigue criterion enables to conclude that the viscoelastic materials can be employed with the aim of increasing the fatigue life of engineering structures due to their efficiency in mitigating the stress levels.